Groundwater Amphipods of the Hyporheic Interstitial: A Case Study from Luxembourg and The Greater Region - Dieter Weber; Alexander M. Weigand (Diversity, 2023)
Hyporheic interstitials are ecologically dynamic and often neglected aquatic environments. In this study, groundwater amphipods (Niphargidae, Pseudoniphargidae and Crangonyctidae) were sampled in hyporheic interstitials throughout Luxembourg and The Greater Region and specimens were analyzed by DNA barcoding. Sites characterized by gravel or coarse sand and high flow velocities of incoming water were the most species- and specimen-rich. A total of 11 species were detected, of which the Niphargus aquilex lineage EF of the N. aquilex cryptic species complex and juveniles of N. schellenbergi dominated the data set, but an unknown lineage of the N. aquilex-complex was also found. Some regions appeared to be devoid of groundwater amphipods. We hypothesize that underlying sandstone formations resulting in low sediment porosity may prevent physical colonization, but also that historical water pollution may have a long-lasting effect, either through the persistence of contaminants in the sediment or low recolonization rates of affected populations. In summary, our approach expanded regional species inventories, confirmed known occurrences, and validated previously questionable or historical morphology-based detections. In addition, the collection of absence data provided valuable insights into local extinctions. Finally, DNA-based distribution data are needed to gather information on the ecological affinities of groundwater amphipods to understudied hyporheic interstitial environments.